Avaliação de um reator biológigo rotativo de contato (RBC) aplicado ao tratamento de efluente de um abatedouro de suínos e aves. - Schwerz, Bervey (2012)
With the expansion of industrial society, began a intense growth of production of waste, creating a latent issue, referring to allocate up correctly all waste generated during the manufacturing process. Specifically, the meat processing generates during its many stages a huge flow of wastewater. An alternative for the treatment of this type of waste are rotating biological contactors. This paper, has for objective, at the construction and application of a RBC to improve performance in the treatment of an industrial effluent from the slaughterhouse of pigs and poultry. It was built a reactor 4L and aerobic sludge was used as inoculum system. The analysis period amounted to 73 days. As results were obtained an efficiency of 84.46% with a removal 1.64 g DBO.m-2 and 88.3% for an HRT of 4 h and surface loading of 124 g DQO.d-1.m-2 for BOD and COD respectively, corresponding to organic matter. On removal of nutrients, the system obtained in an efficiency of 92.02% and a surface charge removed from 8.35 g Nd-1m-2 for nitrogen and 75.66% efficiency and removal of superficial 1.5 g Pd-1.m-2, for analysis of phosphorus. In summary, the RBC could efficiently treat an effluent to obtain satisfactory results in removing the organic load and nutrients.